1986
DOI: 10.1128/aac.30.4.532
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo activity of LY 146032, a new cyclic lipopeptide antibiotic

Abstract: The in vitro activity of LY 146032, a cyclic lipopeptide antibiotic belonging to the class of agents designated A21978C, was compared with those of vancomycin, cefpirome, cefotaxime, and clindamycin against selected gram-positive bacteria. The new drug inhibited all staphylococcal isolates, including methicillin-resistant strains, at concentrations of less than or equal to 1.0 microgram/ml. The activity of LY 146032 was comparable to that of vancomycin against most streptococci, but the latter demonstrated gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
1
3

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(122 citation statements)
references
References 6 publications
2
116
1
3
Order By: Relevance
“…These drugs are similar to vancomycin chemically and in mechanism of action and spectrum of activity. In vitro and in animal models, both are active against methicillin-susceptible and -resistant staphylococci (2,36,57,95). Teicoplanin, which can be given intramuscularly once a day, has been effective in some cases of moderately severe staphylococcal infections.…”
Section: Fusidic Acidmentioning
confidence: 99%
“…These drugs are similar to vancomycin chemically and in mechanism of action and spectrum of activity. In vitro and in animal models, both are active against methicillin-susceptible and -resistant staphylococci (2,36,57,95). Teicoplanin, which can be given intramuscularly once a day, has been effective in some cases of moderately severe staphylococcal infections.…”
Section: Fusidic Acidmentioning
confidence: 99%
“…Another difficult aspect in undertaking NMR structural studies was carrying out characterization of daptomycin under conditions in which the lipopeptide is most active, i.e. in the presence of high concentrations of Ca 2+ [46][47][48]. With the Ca 2+ /daptomycin molar ratio at 1:1 under these conditions, oligomerization occurs, resulting in 14 to 16 monomers forming micelles [35,49,50].…”
Section: Daptomycin and Derivativesmentioning
confidence: 99%
“…The effect of calcium on the action mechanism of DPT was initially reported in 1986 (Eliopoulos et al, 1986). A subsequent study demonstrated that DPT MICs are generally twofold to fourfold lower when tested in broth containing 50 µg mL -1 of calcium (Fuchs, Barry, Brown, 2000).…”
Section: Calcium Concentrationmentioning
confidence: 99%
“…The molecule is obtained from a strain of Streptomyces roseosporus and was originally known as LY 146032 (Debono et al, 1987;Eliopoulos et al, 1986). The action mechanism is physiologic calcium dependent and possibly involves the disruption of amino acid transport by the cell membrane and changes in the cytoplasmic membrane potential (Debono et al, 1987;Koeth, Thorne, 2010;Lu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%